2015
DOI: 10.3846/16111699.2014.976255
|View full text |Cite
|
Sign up to set email alerts
|

Information Technology and Risk Factors for Evaluating the Banking Industry in the Taiwan: An Application of a Value Chain Dea

Abstract: The main purpose of the paper is utilizing a new tool to measure the marginal benefits of information technology on productivity based upon identifying the two-stage best practice frontier. This study utilizes value-chain data envelopment analysis to investigate the effects of Information Technology and the trading activities of financial derivatives on the technical efficiency of a bank's production process through a two-stage analytical study with a firm-level data set. We find the impact of indicators relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…In this analysis, inputs are, for example, labor, physical capital, purchased funds, deposits, and outputs, short, medium, and long-term loans (Kao and Liu 2014), bonds, and off-balance sheet assets (Tsionas et al 2015), revenue-generating assets (Mamatzakis et al 2015), income (Desta 2016;Abdul-Wahab and Haron 2017). Investment in technology can also be considered as input, and the number of ATMs can be used as a proxy (Wang and Lu 2015).…”
Section: Efficiencymentioning
confidence: 99%
See 1 more Smart Citation
“…In this analysis, inputs are, for example, labor, physical capital, purchased funds, deposits, and outputs, short, medium, and long-term loans (Kao and Liu 2014), bonds, and off-balance sheet assets (Tsionas et al 2015), revenue-generating assets (Mamatzakis et al 2015), income (Desta 2016;Abdul-Wahab and Haron 2017). Investment in technology can also be considered as input, and the number of ATMs can be used as a proxy (Wang and Lu 2015).…”
Section: Efficiencymentioning
confidence: 99%
“…To analyze the determinants of efficiency, the Tobit methodology is used, since efficiency is a scale from zero to one, this being the most appropriate methodology, following Defung et al (2016) and Wang and Lu (2015). Thus, according to these authors, the model is as follows:…”
Section: Cost or Economic Efficiencymentioning
confidence: 99%
“…DEA is an analytical tool used for business effectiveness evaluations in many areas (Hadad, Friedman, & Israeli, 2005;Wang & Lu, 2015;Yao, Han, & Luo, 2010;Zhu, 2009). DEA is also known to be able to rank different models (Jablonksy, 2016) evaluate risks of the units surveyed (Aldamak & Zolfaghari, 2017;Chang, Chung, Sun, & Yang, 2012), and analytically rank risks (Sheludko & Kirova, 2018).…”
Section: Literature Review On Dea Methodsmentioning
confidence: 99%
“…The model was also adopted by Chiu and Huang (2011), who evaluated the operational and profitability efficiencies of tourist hotels in Taiwan using the model. More recently the model has been applied in evaluating the impact of IT and risk performance in commercial banks in Taiwan (Wang & Lu, 2015). Kao (2014) summarised a wide range of network DEA studies that were based on problems identified and the models that have been developed and applied to them.…”
Section: Data Envelopment Analysis In Performance Measurementmentioning
confidence: 99%